An overview of the molecular mechanisms underlying development and progression of bicuspid aortic valve disease. (July 2019) - Balistreri, Carmela Rita; Forte, Maurizio; Greco, Ernesto; Paneni, Francesco; Cavarretta, Elena; Frati, Giacomo; Sciarretta, Sebastiano
Abstract: Bicuspid aortic valve (BAV) is a common congenital heart malformation frequently associated with the development of aortic valve diseases and severe aortopathy, such as aortic dilatation, aneurysm and dissection. To date, different genetic loci have been identified in syndromic and non- syndromic forms of BAV. Among these, genes involved in the regulation of extracellular matrix remodelling, epithelial to mesenchymal transition and nitric oxide metabolism appear to be the main contributors to BAV pathogenesis. However, no- single gene model explains BAV inheritance, suggesting that more factors are simultaneously involved. In this regard, characteristic epigenetic and immunological profiles have been documented to contradistinguish BAV individuals. In this review, we provide a comprehensive overview addressing molecular mechanisms involved in BAV development and progression.